2020
DOI: 10.21203/rs.3.rs-74822/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Restructuring citrus endophytic diversity through potential indigenous endophytes could eliminate huanglongbing pathogen Candidatus Liberibacter asiaticus

Abstract: Background Huanglongbing (HLB) is a major botanical pandemic of citrus crops caused by Candidatus Liberibacter asiaticus (Clas). It is important to understand the different mechanisms involved in interaction of pathogen with plants to develop novel management strategy against HLB. However, until now there has been no control strategy to manage this disease in vitro and on large scale in citrus grove. We found that, indigenous endophyte Bacillus subtilis L1-21, a patented strain isolated from healthy citrus tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Diseased leaves were selected from HLB-affected citrus plants grown under greenhouse of Yunnan Agricultural University, China and confirmed through qPCR using primer sequence CQULA04F 5 TGGAGGTGTAAAAGTTGCCAAA 3 , CQULA04R 5 CCAAC-GAAAAGATCAGATATTCCTCTA 3 . Half leaf methods were applied as designed by Munir et al [24], with some modifications. Leaves were further treated with different candidate endophytes.…”
Section: Antagonistic Effect Of Candidate Bacillus Strains Against Xanthomonas Citri Subsp Citrimentioning
confidence: 99%
See 1 more Smart Citation
“…Diseased leaves were selected from HLB-affected citrus plants grown under greenhouse of Yunnan Agricultural University, China and confirmed through qPCR using primer sequence CQULA04F 5 TGGAGGTGTAAAAGTTGCCAAA 3 , CQULA04R 5 CCAAC-GAAAAGATCAGATATTCCTCTA 3 . Half leaf methods were applied as designed by Munir et al [24], with some modifications. Leaves were further treated with different candidate endophytes.…”
Section: Antagonistic Effect Of Candidate Bacillus Strains Against Xanthomonas Citri Subsp Citrimentioning
confidence: 99%
“…Their effective use will reduce the dependence on chemical fertilizers and pesticides [23]. Keeping the importance of previous studies in citrus plants using endophyte L1-21, remarkable changes were observed in healthy and diseased citrus plants [24]. Metabolomics approaches were conducted to gain information about the molecular mechanism of citrus plant to defend themselves against CLas [25].…”
Section: Introductionmentioning
confidence: 99%